THE EFFECT OF THE USE OF STORY MAP ON STUDENTS’ NARRATIVE TEXTS READING COMPREHENSION - Aini, Nur; Sudarsono, Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract    This research was conducted based on the observation of reading comprehension to the Year-8 students of MTs. Darul Ulum Kubu Raya in Academic Year 2016/2017. The purposes of the research are to investigate the significance of teaching reading comprehension in narrative text by using story map and to investigate the effectiveness of teaching reading comprehension in narrative text by using story map.It was pre experimental research. It involved pre-test, treatment, and post-test. There were 26 students in this research. The data were quantitative participating.This research found that the treatment improved the students’ ability in comprehending a narrative text reading. The mean score of pre-test was 57,88 and the mean score of post-test was 70,53. The improvement is significant statistically. It can be seen from value that was lower than the t-table -2,093 > -8,72. The effect size of using story map to the students’ reading comprehension on narrative text is 0,73 (Moderate).    Key Words: Effectiveness, Narrative, Story Map